Uncontrolled development and the planning process of local authorities: A case study of Mutawatawa Growth Point in Uzumba Maramba Pfungwe District. - Kasuso, Mukai (Midlands State University, 2017)
The aim of this study was to review proliferation of uncontrolled development at MGP in UMP district and shed some light on the characteristics of infrastructure there. Concern over uncontrolled development within the urban set up has often been used as the justification for establishing what are regarded as minimum acceptable standards of development. Properly planned urban development is a key to achieving sustainable environment. Urban planning therefore becomes important as local authorities develop their urban areas. For Uzumba Maramba Pfungwe RDC to maintain its land use allocation pattern of its urban area, it needs to assess, monitor and control the trend and the pattern of development as they occur since uncontrolled development (slum developments) may mar the beauty and sustainability of the urban area. This paper focuses on assessing and analyzing urban development using a qualitative analysis on the existing developments within Uzumba Maramba Pfungwe District with particular attention on the Growth point of Mutawatawa. Regardless of the multiplicity of town planning regulatory frameworks passed from pre and post independence Zimbabwe, Regional, Town and Country planning guide urban development in most towns. This research uses case-study analysis to explore the effects of uncontrolled development on the planning process of MGP in Uzumba Maramba Pfungwe district. The sample size for the study was forty nine (49). Interviews were held with key personnel in UMP RDC Council, District Administrator’s office, Public works department, National Housing department, residents and the business community to ascertain the effects of unregulated development on the planning process. Questionnaires were also used to complement the data collected from interviews. The data was presented and analysed through the use of tables, pie charts, bar graphs and photographs. Amongst its key findings, the research observed that uncontrolled development poses so many effects to the whole planning process of the local authority. It results in the waste of effort and resources as the planners would need to either alter the existing plans as they try to regulate the uncontrolled development. Causes of uncontrolled development were identified as lack of development monitoring, high inspection fees, manpower shortage, and laxity on the use of development instruments. The data analysed reveals that the physical infrastructure in place is exceptionally poor. However, the conciliatory planning approach adopted comes with its own problems, for example: uncoordinated development, land zoning challenges, skewed land use distribution, poor townscape, urban sprawl and sub standard buildings. In the light of the findings of the study the researcher recommends regular assessment on construction activities, enforcement of development by laws, approval of development plans, imposition of stiffer penalties on illegal developers, involvement of stakeholders in the planning process, imposition of affordable inspection and approval fees, upholding of council procedures on land acquisition and development, development of a developmental plan and increasing the planning department manpower as solutions to uncontrolled development.